2020
DOI: 10.26226/morressier.5f0c7d3058e581e69b05d15a
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Did the Recognition of Operating Leases Cause a Decline in Equity Valuations?

Abstract: We examine whether investors react to a significant change in financial statements absent a significant change in underlying economics. Beginning in 2019, ASC 842 requires the recognition of operating leases, which were previously only disclosed in the footnotes. This change in accounting standard has no effect on firms' economics but results in firms with significant operating leases recognizing a considerable increase in debt. We find that firms with significant operating leases, on average, earn negative re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…With regard to the debt ratio (= total liabilities / total assets), although both liabilities and assets would increase in the same amount, if the debt ratio previously was lower than 1 (which is commonly the case, unless the company has negative equity), the ratio will have to increase. Milian & Lee [2], using preliminary quarterly results from the 2019 financial year, found that the increase in leverage for companies with a high intensity of operating leases can decrease…”
Section: Leverage Ratiosmentioning
confidence: 99%
“…With regard to the debt ratio (= total liabilities / total assets), although both liabilities and assets would increase in the same amount, if the debt ratio previously was lower than 1 (which is commonly the case, unless the company has negative equity), the ratio will have to increase. Milian & Lee [2], using preliminary quarterly results from the 2019 financial year, found that the increase in leverage for companies with a high intensity of operating leases can decrease…”
Section: Leverage Ratiosmentioning
confidence: 99%